Rapid, transient expression of fluorescent fusion proteins in tobacco plants and generation of stably transformed plants - Sparkes, I.A.; Runions, J.; Kearns, A.; Hawes, C.
Expression and tracking of fluorescent fusion proteins has revolutionized our understanding of basic concepts in cell biology. The protocol presented here has underpinned much of the in vivo results highlighting the dynamic nature of the plant secretory pathway. Transient transformation of tobacco leaf epidermal cells is a relatively fast technique to assess expression of genes of interest. These cells can be used to generate stable plant lines using a more time-consuming, cell culture technique. Transient expression takes from 2 to 4 days whereas stable lines are generated after approximately 2 to 4 months.
Keywords: ARTICLECELL FUSIÓN; CELL TRANSFORMATION; CULTURE TECHNIQUE; ENDOPLASMIC RETICULUM; GENE EXPRESSION; GOLGI COMPLEX; IN VIVO STUDY; NONHUMAN